2022
DOI: 10.25259/apos_134_2021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of maxillary and mandibular effective base length, arch length and dental crowding in different vertical growth pattern

Abstract: Objectives: The objectives of the study were to assess, measure, and correlate the maxillary and mandibular effective base length, arch length to the amount of dental crowding in different vertical growth pattern patients. Materials and Methods: Sample comprising 100 pre-treatment lateral cephalograms and study models (age group – 16–25 years) was randomly selected. The sample was divided into two groups, that is, clockwise (50) and anticlockwise (50) rotation based on the measurement of the gonial angle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Many studies have found a correlation between crowding and the direction of mandibular rotation. Extreme mandibular rotation has been linked to increased crowding, and crowding is also brought on by some growth/skeletal patterns at the start of adolescence [ 28 ]. Other factors that should not be underestimated for the diagnosis of crowding are the changes in facial morphology brought on by growth or orthodontic treatment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found a correlation between crowding and the direction of mandibular rotation. Extreme mandibular rotation has been linked to increased crowding, and crowding is also brought on by some growth/skeletal patterns at the start of adolescence [ 28 ]. Other factors that should not be underestimated for the diagnosis of crowding are the changes in facial morphology brought on by growth or orthodontic treatment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%